2013
DOI: 10.1371/journal.pone.0064751
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Antioxidant and Antiulcer Activity of Parkia speciosa Ethanolic Leaf Extract against Ethanol-Induced Gastric Ulcer in Rats

Abstract: BackgroundThe current study was carried out to examine the gastroprotective effects of Parkia speciosa against ethanol-induced gastric mucosa injury in rats.Methodology/Principal FindingsSprague Dawley rats were separated into 7 groups. Groups 1–2 were orally challenged with carboxymethylcellulose (CMC); group 3 received 20 mg/kg omeprazole and groups 4–7 received 50, 100, 200 and 400 mg/kg of ethanolic leaf extract, respectively. After 1 h, CMC or absolute ethanol was given orally to groups 2–7. The rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 27 publications
10
91
0
5
Order By: Relevance
“…The high GUI observed in ethanol-treated rats indicates a potent ulcerogenic effect of ethanol which is in harmony with previous studies [36][37][38]. The significant decrease in the GUI of ethanoltreated rats upon pretreatment with crocin indicates a marked gastroprotective ability for crocin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high GUI observed in ethanol-treated rats indicates a potent ulcerogenic effect of ethanol which is in harmony with previous studies [36][37][38]. The significant decrease in the GUI of ethanoltreated rats upon pretreatment with crocin indicates a marked gastroprotective ability for crocin.…”
Section: Discussionsupporting
confidence: 90%
“…A similar pattern of ethanol-induced alterations in oxidative stress biomarkers was recently reported [38]. Oxidative stress results from an imbalance between the generated ROS and the available antioxidant capacity.…”
Section: Groupssupporting
confidence: 84%
“…TNF-α and IL-1β, inflammatory cytokines, chemokines and other mediators contribute to the inflammation process as an immune response [39,40]. It was reported in previous studies that the ROS and TNF-α levels increased the apoptosis in the gastric tissue [3,5,41]. In previous studies, it has been shown that salusin-β might increase the inflammatory factors by increasing the I-κBa/NF-κB signal pathway activation [21].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying ethanol-induced gastric ulcer are not fully defined. However, some evidence have been offered to demonstrate that proinflammatory cytokines, oxidative stress and apoptosis play important roles in the pathogenesis of ulcer [3][4][5][6][7]. Ethanol inhibits the mitochondrial electron transfer system and increases reactive oxygen species (ROS) production, thus causing cellular injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…It decreases discharge of bicarbonate, suppresses the production of gastric mucosa (Al Batran et al, 2013). This action destroys the protective mucosal layer and renders the cells of stomach lining exposed to proteolytic and hydrolytic actions of gastric acid (Sener et al, 2004).…”
Section: Discussionmentioning
confidence: 99%